Digital Social Innovation and Urban Space: A Critical Geography Agenda - Chiara Certomà (Urban Planning, 2020)
Digital Social Innovation (DSI) is a new concept referring to social innovation initiatives that leverage digital technologies potentiality to co-create solutions to a wide range of social needs. These initiatives generally take place in urban contexts. However, in the existing literature, scarce attention is devoted to the spatial dimensions and the social, cultural or political space-related effects of DSI practices. This article suggests that a critical geography perspective can address these gaps. After a review of existing relevant contributes, the article elaborates a research agenda for a critical geography of DSI. This articulates along four research lines, including the emergence of DSI networks, the (re)production of DSI processes and socio-cultural urban space, the representations of DSI practices and the power relationships these mobilise.